A eficácia simbólica nos sistemas tradicionais de saúde - José Fialho (Cadernos de Estudos Africanos)
The health-care system in Mozambique includes two ethno-medical sub-systems: conventional medicine and traditional medicine. The traditional medicine sub-system combines the use of pharmaceutical products with the (re)activation of social relations and representations which turn it into a complex field of interpretation, in terms of both diagnosis and therapy. It is by analysing this interaction that we are able to come to a possible understanding of their efficacy.